CHARACTER ASSOCIATION AND PATH COEFFICIENT ANALYSIS FOR GRAIN YIELD AND ITS COMPONENTS IN MAIZE (Zea mays L.) - SRINIVASA CHARY. D and FARZANA JABEEN, PRAVEEN KUMAR. G, SUNIL. N, SEKHAR. J. C (The Journal of Research, PJTSAU, 2023)
An investigation was carried out with the objective of assessing the magnitude of the association between grain yield and its component characters. Thirty nine genotypes consisting of eight parents, twenty eight crosses obtained by crossing eight inbred lines using Diallel mating design (without reciprocals), and three checks were evaluated in randomized block design with three replications. In the present study the results indicated that the genotypic correlation coefficient is greater than the corresponding phenotypic correlation coefficient for all the traits studied which indicates that though there is strong inherent association between characters studied, its expression is masked due to influence of environment. Correlation coefficient analysis of grain yield per plant showed strong and significant positive association with ear length, number of kernels per row, ear diameter, plant height, 100-kernel weight, ear height and number of kernel rows per ear at genotypic and phenotypic level. However, days to 50% tasseling and days to 50% silking exhibit negative correlation with grain yield, while shelling percentage showed non significant positive. Path coefficient analysis revealed, the number of kernels per row exerted maximum positive direct effect on grain yield per plant followed by ear length, days to maturity, ear diameter, 100-kernel weight and shelling percentage. The high direct effects of number of kernels per row and ear length appeared to be the main factor for their strong association with grain yieldper plant. Hence, direct selection for these traits would be effective for grain yield improvement in maize.